A numerical study on the hydrodynamics of a floating tidal rotor under the combined effects of currents and waves - Zilic de Arcos, F; Vogel, CR; Willden, RHJ (Elsevier, 2023)
This work examines the hydrodynamics of a 20 m diameter axial-flow tidal rotor supported by a catamaran-style floating platform. Using a time-domain seakeeping model of the float, coupled with a dynamic model of the rotor based on blade-element momentum theory, the floating tidal turbine was analysed under the combined effects of following waves and currents. The rotor loads were analysed in scenarios with and without platform motions, starting from equivalent initial conditions. While the results show that mean power and thrust are not significantly affected, thrust and power fluctuations are substantial for the rotor under waves with and without platform motions. When platform motions were considered, amplification and reduction of load fluctuations were observed at different wave periods. These effects are associated with the phase interactions between waves and platform motion response. The reductions in thrust and power fluctuations at certain ranges of wave periods suggest that platform motions do not necessarily have an adverse impact on the operation of floating tidal rotors and could potentially be exploited to reduce fatigue damage and improve the quality of power delivery. The amplification of transient loads, on the contrary, suggests that consideration is required when designing floating systems to avoid potentially damaging effects.